Alterations of Bruch’s membrane in pseudoxanthoma elasticum. - Guerriero, S.; Milano, A.; Garofalo, L. (European Journal of Pediatric Dermatology, 2011)
This is a 36-year-old woman sent by the ophthalmologists due to the presence of skin lesions of the folds, mainly in the latero-cervical region. Her family history showed similar changes in a patient's brother, while her parents, who were not consanguineous, did not present significant alterations of the skin. The skin changes of the patient started in the second decade of life. The physical examination highlighted level with the folds of the neck, armpits and groin, yellowish, close to each other papules (Fig. 1), with a flat surface and partially confluent in linear plaques. No significant inelastic folds, calcifications or blackheads, nor mucous papules were observed. The patient was followed in the Ophthalmology Department due to angioid streaks of Bruch's membrane (Fig. 2, 3). Her family history, the clinical signs of skin and eye led to the final diagnosis of pseudoxanthoma elasticum. The patient was sent to cardiology and gastroenterology examination.